The Writing Public Participatory Knowledge Production in Enlightenment and Revolutionary France - Bond, Elizabeth Andrews (Cornell University Press, 2021)
Inspired by the reading and writing habits of citizens leading up to the French Revolution, The Writing Public is a compelling addition to the long-running debate about the link between the Enlightenment and the political struggle that followed. Elizabeth Andrews Bond scoured France's local newspapers spanning the two decades prior to the Revolution as well as its first three years, shining a light on the letters to the editor. A form of early social media, these letters constituted a lively and ongoing conversation among readers. Bond takes us beyond the glamorous salons of the intelligentsia into the everyday worlds of the craftsmen, clergy, farmers, and women who composed these letters. As a result, we get a fascinating glimpse into who participated in public discourse, what they most wanted to discuss, and how they shaped a climate of opinion. The Writing Public offers a novel examination of how French citizens used the information press to form norms of civic discourse and shape the experience of revolution. The result is a nuanced analysis of knowledge production during the Enlightenment. Thanks to generous funding from The Ohio State University Libraries and its participation in TOME (Toward an Open Monograph Ecosystem), the ebook editions of this book are available as Open Access (OA) volumes, available on the Cornell University Press website and other Open Access repositories.